2019
DOI: 10.1002/path.5274
|View full text |Cite
|
Sign up to set email alerts
|

YWHAZ amplification/overexpression defines aggressive bladder cancer and contributes to chemo‐/radio‐resistance by suppressing caspase‐mediated apoptosis

Abstract: The objective of this study was to characterize the oncogenic actions of a recently identified cancer‐associated gene YWHAZ (also named as 14‐3‐3 ζ/δ) in urothelial carcinomas of the urinary bladder (UCUB). A genome‐wide study revealed YWHAZ to be involved in the amplicon at 8q22.3, and its genetic amplification was detected predominantly in muscle‐invasive bladder cancer (MIBC). Immunohistochemical staining confirmed the association of YWHAZ overexpression with higher tumor stages, lymph node/vascular invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In this regard, epigenetic silencing of miR-193a could result in upregulation of YWHAZ and tumor invasion in vitro and in vivo . As YWHAZ was previously found to be involved in cancer metastasis ( 24 , 25 ), overexpression of YWHAZ could enhance gastric cancer invasion in vitro and in vivo . Clinically, higher miR-193a methylation, and YWHAZ expression, was observed in patient tissue samples with H. pylori infection, suggesting that H. pylori mediated STAT3 activating might be responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this regard, epigenetic silencing of miR-193a could result in upregulation of YWHAZ and tumor invasion in vitro and in vivo . As YWHAZ was previously found to be involved in cancer metastasis ( 24 , 25 ), overexpression of YWHAZ could enhance gastric cancer invasion in vitro and in vivo . Clinically, higher miR-193a methylation, and YWHAZ expression, was observed in patient tissue samples with H. pylori infection, suggesting that H. pylori mediated STAT3 activating might be responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 89%
“…Combination of three microRNA databases found that there are 97 common targets with predicted miR-193a binding site. One of the downregulated targets, YWHAZ , which has been previously found to be involved in metastasis ( 24 , 25 ), was chosen for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…This therapeutic avenue might be combined together with different immunomodulatory drugs, enhancing their effect [ 53 ]. In the case of 14-3-3ζ/δ, Yu et al [ 54 ] reported that immune-associated genes involved in interferon signaling, TLR-4 signaling, inflammasome network, antigen presentation/TCR recognition, and CD28 co-stimulation were found significantly downregulated in patients with urothelial carcinomas of the urinary bladder (UCUBs) presenting YWHAZ amplification/overexpression. However, there is no evidence of YWHAZ immunomodulation in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al revealed that TFDP1/E2F1 transcriptional activity played an important role in NSCLC [ 37 ]. YWHAZ (also named 14-3-3ζ), acts as a major hub protein for many signal transduction pathways [ 38 , 39 ]. YWHAZ was frequently shown to be upregulated in several types of cancers, and its overexpression was often correlated with unfavorable prognosis of cancer patients [ 40 – 43 ].…”
Section: Discussionmentioning
confidence: 99%